2010 IEEE Frontiers in Education Conference (FIE) 2010
DOI: 10.1109/fie.2010.5673551
|View full text |Cite
|
Sign up to set email alerts
|

Work in progress — Engaging students in thermodynamics with Engineering Scenarios

Abstract: This NSF CCLI Phase II project is focused on addressing improvements in student pedagogy and educational materials for the thermodynamics curriculum.The project intends to complete the development of the "Engineering Scenario" concept as a textbook supplement based on actual engineering facilities and real-world problems. The material is based on an expanded case study format and constructed in a web based format, allowing extensive integration of narrative, pictures, video, and web links to expand the backgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Accompanying supplementary and background information promotes increased inquiry-based or student-centered learning, better addresses student real world expectations, and leads to an increase in overall student engagement. The development of the Engaged in Thermodynamics material has been detailed in a number of papers [2,3]. There is great pedagogical flexibility in allowing varying levels of use by the faculty member.…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying supplementary and background information promotes increased inquiry-based or student-centered learning, better addresses student real world expectations, and leads to an increase in overall student engagement. The development of the Engaged in Thermodynamics material has been detailed in a number of papers [2,3]. There is great pedagogical flexibility in allowing varying levels of use by the faculty member.…”
Section: Introductionmentioning
confidence: 99%
“…The assessments also indicated that there was a link between student performance and engagement 1 . Further assessment during Phase 2 demonstrated that the impact was highly dependent on how the material was used and what the overall course format was.…”
Section: History Of the Projectmentioning
confidence: 99%